2020
DOI: 10.1002/ece3.5964
|View full text |Cite
|
Sign up to set email alerts
|

Opening the door to greater phylogeographic inference in Southeast Asia: Comparative genomic study of five codistributed rainforest bird species using target capture and historical DNA

Abstract: Indochina and Sundaland are biologically diverse, interconnected regions of Southeast Asia with complex geographic histories. Few studies have examined phylogeography of bird species that span the two regions because of inadequate population sampling. To determine how geographic barriers/events and disparate dispersal potential have influenced the population structure, gene flow, and demographics of species that occupy the entire area, we studied five largely codistributed rainforest bird species: Arachnothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 117 publications
(157 reference statements)
3
13
0
Order By: Relevance
“…Earlier studies found that B. atriceps exhibits little to no population structure across most of its range, except between eastern and western Indochina, and between Maratua Island the rest of Sundaland (Chua et al, 2015; Dejtaradol et al, 2015; Lim et al, 2020). In their UCE study, Lim et al (2020) included only a single grey specimen of B. atriceps (from Bawean Island) and found that it barely differed from other populations (they did not compare individuals from Maratua). However, the UCE data of that grey specimen were derived from a toe‐pad sample >100 years old and comprised few complete loci.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies found that B. atriceps exhibits little to no population structure across most of its range, except between eastern and western Indochina, and between Maratua Island the rest of Sundaland (Chua et al, 2015; Dejtaradol et al, 2015; Lim et al, 2020). In their UCE study, Lim et al (2020) included only a single grey specimen of B. atriceps (from Bawean Island) and found that it barely differed from other populations (they did not compare individuals from Maratua). However, the UCE data of that grey specimen were derived from a toe‐pad sample >100 years old and comprised few complete loci.…”
Section: Discussionmentioning
confidence: 98%
“…cf. purpureomaculatus occurs at the Isthmus of Kra (De Bruyn et al, 2005; Hughes et al, 2003; Parnell, 2013), which serves as a biogeographic divide for numerous vertebrate species including reptiles (Grismer et al, 2022; Mulcahy et al, 2017; Olivier S.G. Pauwels et al, 2016; Trivalairat et al, 2022; van Rooijen & Vogel, 2010; Vogel et al, 2012; Zug et al, 2017), amphibians (Buddhachat & Suwannapoom, 2018; Poyarkov et al, 2020; Yodthong et al, 2014), birds (Hughes et al, 2003; Lim et al, 2020), and mammals (Tougard, 2001). Our results also show that phylogeographic structure is latitudinally stratified and consistent with IBD and IBE, with colour polymorphisms appearing to be latitudinally structured as well.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the average heterozygosity of our UCE-derived SNPs is 0.23, similar to that reported in RAD-seq studies of other small mammal populations, including mice of the genera Apodemus In summary, although more research is needed into the substitution rate of UCE loci and its effect on demographic inferences, our results show that UCE capture methods can be used for finescale population genomics, providing an additional tool for studying nongenome-enabled species. UCE capture produces data with similar information content and has several benefits over RAD-seq, including: (i) enabling the direct comparison of inferences drawn from the same set of loci across species, allowing conclusions to be drawn about the effects of historical processes on diverse taxa (Lim et al, 2020); (ii) offering repeatability such that studies can compare inferences for the same species across time and geographical regions (Harvey et al, 2016); and (iii) enabling the use of low-quality DNA, including DNA derived from historical museum specimens (Hawkins et al, 2016;Lim & Braun, 2016;Lim et al, 2020;Tsai et al, 2019).…”
Section: Uces For Fine-scale Population Genomicsmentioning
confidence: 99%